Home Movie as a Text of Cultural Memory - Dikavičiūtė, Ona Kotryna (Semiotika, 2022)
The aim of this article is to define home movie as a text of cultural memory and reveal the dynamics of its meanings in culture. The personal and the collective maintenance and transmission of memory is a complex mechanism that operates within a dynamic cultural model. The analysis of this mechanism considers the way in which something that first appears to be culturally irrelevant – a private home movie of a family – is brought into the public space and circulates as a cultural text contributing to the preservation and formation of cultural memory. The analysis describes home movie in the framework of semiotics and reveals the meaning shifts that occur when private memory texts begin to circulate in a more general cultural context. The mechanism of the dynamics of cultural texts and the problematics of memory are explored using Yuri Lotman’s cultural semiotics approach. The example of Lithuanian director’s Dovilė Šarutytė’s debut feature film A Feature Film About Life (2021) is used to describe in more detail the transformations of meaning that home movies undergo after becoming a cultural text.
Keywords: Lotman; cultural memory; amateur cinema; home movies; archival cinema